Humor usage by sellers and sales performance: The roles of the exploration relationship phase and types of humor. (June 2018) - Lunardo, Renaud; Bompar, Laurent; Saintives, Camille
For sellers, the efficacy of humor to create trusty relationships and achieve performance with buyers remains unknown. Specifically, the question of if – and when – sellers should use humor still deserves examination. To answer this question, this research builds on the four phases that characterize long-term relationships (exploration, buildup, maturity, and decline) to argue that humor might be inefficient when used in the exploration phase. Two studies conducted among buyers ( n  = 322) then reveal that although constructive humor has overall positive effects on the performance of the sellers through a mediating effect of trust, this effect is not observed during the exploration phase. The other type of humor – offensive humor – has a negative effect regardless of the phase in which it is used. Taken together, these results first indicate that sellers may gain from using humor only if the relationship with their buyers is not at the exploration phase since this particular phase is the only one when a negative effect of humor on trust and subsequent performance is observed. Furthermore, these results indicate that offensive should be avoided in all the relationship phases.